Musicianship Influences Language Effect on Musical Pitch Perception - Choi, William (Frontiers in Psychology, 2021)
Given its practical implications, the effect of musicianship on language learning has been vastly researched. Interestingly, growing evidence also suggests that language experience can facilitate music perception. However, the precise nature of this facilitation is not fully understood. To address this research gap, I investigated the interactive effect of language and musicianship on musical pitch and rhythmic perception. Cantonese and English listeners, each divided into musician and non-musician groups, completed the Musical Ear Test and the Raven’s 2 Progressive Matrices. Essentially, an interactive effect of language and musicianship was found on musical pitch but not rhythmic perception. Consistent with previous studies, Cantonese language experience appeared to facilitate musical pitch perception. However, this facilitatory effect was only present among the non-musicians. Among the musicians, Cantonese language experience did not offer any perceptual advantage. The above findings reflect that musicianship influences the effect of language on musical pitch perception. Together with the previous findings, the new findings offer two theoretical implications for the OPERA hypothesis—bi-directionality and mechanisms through which language experience and musicianship interact in different domains.